Ammonium bromide as a saturable absorbing device for ultrafast photonics - Mohd Yusoff, Norita; Chyi, Josephine Liew Ying; Ng, Eng Khoon; Lee, Han Kee; Mayzan, Mohd Zul Hilmi; Alresheedi, Mohammed Thamer; Zainol Abidin, Nadiah Husseini; Md Zain, Ahmad Rifqi; Mahdi, Mohd Adzir (Elsevier, 2025)
We demonstrate an ammonium bromide/polydimethylsiloxane (NH4Br/PDMS) composite as a saturable absorbing device, exhibiting a modulation depth of 9.3% and a saturation fluence of 102 μJ/cm2 at 1.56 μm wavelength. The laser cavity design was experimentally optimized by strategically arranging passive optical components, specifically by placing the optical coupler immediately between the amplifying section and the NH4Br/PDMS-based saturable absorber. This laser setup achieved a low threshold power of 20.77 mW and delivered near transform-limited pulses with a narrowest width of 713 fs, producing an average output power of 10.72 mW and a pulse energy of 0.99 nJ. The robustness of the NH4Br-based saturable absorber device was validated through a total monitoring period of 40 h, a damage threshold of greater than 16.40 mJ/cm2, and continued functionality even after three years of fabrication. This work provides a pathway for the transition from laboratory research to commercial applications, and offers a valuable guideline for designing ultrafast pulse fiber laser systems. Since this work focused on optimizing an erbium-doped fiber (HP980 from Lucent Technologies) with a group velocity dispersion of +23 ps2/km, slight modifications might be necessary for other erbium-doped fibers to achieve optimum pulse performance.